A Study of Practical Examinations: Provision and Practices - Karki, Tek Mani (Tribhuvan University Journal, 2020)
Tribhuvan University, Faculty of Education has introduced four-year annual B. Ed. program in 2015. The Department of English Education has of fereda course with theory plus practice in nature each year in this program. One of the courses with this nature is ‘Research Methodology in English Education’, introduced in the fourth year. Concerning the practical portion of this course, this paper highlights the variations of research reports and explores the challenges faced by the subject teachers (internal examiners) and the students selecting five affiliated campuses applying convenient sampling procedure in Bagmati province. Five research reports (one from each campus) selected randomly were analyzed, five teachers and five students (one from each campus) purposively selected were interviewed to gather information, and the data were interpreted thematically. Considerable amount of variation appeared in the research reports in terms of format, content, and citations and referencing style. Challenges occurred when the teachers did not receive clear guidelines from the concerned authorities to uniform the practical works. Students’ irregularities seemed another challenge for quality improvement in research works. The challenges can be minimized by implementing the course guidelines in practice. For this, the concerned authorities can organize several programs to support the teachers and to attract the students attending the classes regularly at the campuses.